Nosocomial diarrheal disease caused by Clostridioides difficile in a national hospital in Lima, Peru - Castillo-Contreras, Ofelia (2020)
Objective: to determine frequency, incidence, and to describe clinical and epidemiological characteristics of patients with nosocomial diarrheal disease caused by Clostridioides difficile in Edgardo Rebagliati-Martins National Hospital in Peru, between April to July 2019. Material and methods: this is an observational and cross-sectional study that was performed in Internal Medicine, Intensive Care, Hematology, Gastroenterology, and Emergency services. Active surveillance of patients more than 18-years old who had three or more non-formed stools in a 24-hour period at 48-hours after being admitted to the hospital. A diagnostic algorithm was used, including glutamate dehydrogenase and A and B C. difficile fecal toxins. In case of discordant results, nucleic acid amplification for toxin producing genes tests were performed. Results: out of 107 patients with nosocomial diarrheal disease, 12 were positive for C. difficile, with 11.2% frequency (95% CI: 6.44 – 18.82). One patient was NAP1-BI-027 positive. The maximum incidence was found in the hematology service (5.54 x 10000 patientsday). Seven (7/12, 58.3%) patients were male and average age was 64.58 ± 21.34 years. The most frequently prescribed antibacterial agent prior to the diarrheal disease was meropenem (9/12, 75%). Only two patients had received clindamycin. Most patients (8/12, 66.7%) had an initial non severe episode. Overall mortality was 28% (95% CI: 20.27–37.38) and four deceased patients had C. difficile infection. Conclusions: The frecuency of nosocomial diarrheal disease caused by C. difficile in our institution was lower than that reported in another public hospital in Lima. Rational use of antibacterial agents and preventative measures may explain these findings.